Prognostic Significance of Serum Tumor Markers in Patients with Advanced-stage NSCLC Treated with Pemetrexed-based Chemotherapy - Fiala, Ondrej; Pesek, Milos; Finek, Jindrich; Svaton, Martin; Sorejs, Ondrej; Bortlicek, Zbynek; Kucera, Radek; Topolcan, Ondrej (Anticancer research, 2016)
BACKGROUND: Tumor biomarkers represent effective tools for diagnostics and follow-up monitoring of patients with non-small cell lung cancer (NSCLC). We focused on evaluating the predictive and prognostic role of the seven following tumor biomarkers: carcinoembryonic antigen (CEA), cytokeratin-19 fragment (CYFRA 21-1), fragments of cytokeratin 8, 18 and 19 (MonoTotal), neuron-specific enolase (NSE), chromogranin A, thymidine kinase (TK) and squamous cell carcinoma antigen (SCCA) in patients with advanced-stage NSCLC treated with pemetrexed-based chemotherapy. PATIENTS AND METHODS: In total, 114 patients with advanced-stage (IIIB or IV) non-squamous NSCLC treated with pemetrexed-based chemotherapy (monotherapy or combination with a platinum derivative) were included. Comparison of progression-free (PFS) and overall survival (OS) according to the level of assessed tumor markers was performed using the log-rank test. RESULTS: We recorded significantly shorter OS for patients with high pretreatment levels of CYFRA 21-1 (10.3 vs. 23.4 months; p<0.001), NSE (1.6 vs. 13.5 months; p=0.003) and TK (11.3 vs. 23.4 months; p=0.003). CONCLUSION: CYFRA 21-1, NSE and TK are feasible biomarkers for estimation of a patient's overall prognosis, however, none of the measured serum tumor markers were able to predict the efficacy of pemetrexed-based chemotherapy.
Keywords: dospělí; nádorové biomarkery; pemetrexed; Prognosis; prognosis; senioři nad 80 let; Biomarkers, Tumor; Humans; nemalobuněčný karcinom plic; lidé středního věku; Lung Neoplasms; Aged, 80 and over; Middle Aged; Pemetrexed; prognóza; mužské pohlaví; nádory plic; Adult; Disease Progression; tumor marker; ženské pohlaví; NSCLC; Carcinoma, Non-Small-Cell Lung; lidé; Lung cancer; Aged; senioři; progrese nemoci; Male; Female